COMMERCIAL RIGHTS AS A MAIN COMPONENT LIBERALIZATION OF ECONOMIC ACTIVITIES IN THE INDUSTRYAIR TRANSPORT - Bezzubov, Dmytro; Dobkina, Kateryna; Klyuyeva, Yevgeniya; Vitko, Olexander (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to analyze the problems of ensuring the commercial rights of aviation enterprises from the standpoint of the organizational, legal and economic component of the enterprise, to outline models for ensuring compliance with commercial rights in the activities of aviation enterprises, to develop a universal model for ensuring "freedom of air" in the activities of aviation enterprises during cargo transportation. Research methods: in order to achieve scientific objectivity, the authors used a set of research methods that are used in modern legal science. The basis of the scientific article is scientific methods and principles inherent in both the general theory of law and the science of international law with its specific features. Comparative legal and formal legal research methods are used in the work. With the help of the formal legal method, the analysis of the texts of the first international conventions on civil aviation, the Chicago Convention on Civil Aviation of 1944, the Agreement on International Air Transport and the Agreement on Transit on International Air Lines of 1944, normative legal acts of Ukraine was carried out. This method was also used when defining the concepts of "access to the air transport market", "commercial rights" and in the process of researching Ukraine’s position on the liberalization of international air transport. This is explained by the fact that the study of the internal structure of legal norms, analysis of sources of law, systematization and interpretation of normative legal material is characteristic of the formal legal method. In general, the research is based on the principle of methodological pluralism, according to which the analysis must rely on a number of scientific methods, and not give exclusive preference to one of them. Results: the study of the issue of the legal foundations of the administration of the problem of commercial rights is part of the study of the problems of applied economic science, philosophy of law, economic and international economic law. The results of the research presented in this scientific article make it possible to determine the next steps in developing the problems of the development of legal science and the organizational and legal component of ensuring "freedom of the air" in the activities of aviation enterprises. Discussion: problems of liberalization of air transport are part of studies in aviation and economic law; the obtained scientific results allow us to assert the existence of connections between the degree of liberalization and the economic efficiency of the aviation enterprise.